Analisis Implementasi Kurikulum Merdeka di Sekolah Dasar Studi Kualitatif di SDIT Banten Islamic School - Ibtihal, Aqila Azharrani; Firdaus, M. Arie; Zohriah, Anis; Bachtiar, Machdum (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
Education management is an important component in improving the quality and effectiveness of the education system. This article aims to analyze the implementation of the Merdekan Curriculum at SDIT Banten Islamic School, focusing on the freedom of curriculum management, the involvement of teachers and students, and its impact on learning outcomes. Using a lecture approach, data was collected through in-depth interviews with principals, teachers, and students, as well as direct observation of the learning process. The collected data was analyzed using thematic analysis methods to identify relevant patterns and themes. The results of the study show that the implementation of the Independent Curriculum at SDIT Banten Islamic School is running well, there are aspects of freedom in curriculum management and student involvement that are most empirically prominent. Teachers show creativity in designing learning according to student characteristics, while students feel more involved and motivated in the learning process. This study recommends that schools can continue to improve the benchmark for teachers in designing innovative and responsive curriculums to student needs. Thus, the implementation of the Independent Curriculum is expected to create a more effective and inclusive education system.